Availability of Macronutrients & Sulphur and their Relationship with Physico-chemical Properties in Lateritic Soils of Birbhum District, West Bengal - Sahu, Mamta; C. P, Mohammed Nisab; Mondal, Suchhanda (International Journal of Economic Plants, 2022)
The present study was undertaken during 2017–18 at Palli Siksha Bhavana, Visva-Bharati, West Bengal, India to characterize the lateritic soils of Birbhum district, West Bengal, India to investigate the status of macronutrients and sulphur and its relationship with soil physico-chemical properties. Altogether 100 soil samples were collected from different mouzas of five different blocks (Mayureswar, Nalhati-1, Bolpur, Md Bazar and Rajnagar) of Birbhum district of West Bengal, India. Results of the study indicated that soils of different blocks of Birbhum district were sandy loam to sandy clay loam in texture with moderately to strong acidic in reaction.Electrical conductivity was within normal limits. Soils showed deficiency in organic carbon (OC) content. Most of the soil showed low to medium in available N content. Available K content showed medium category whereas soils under study was poor in available P and available sulphur. The pH of the collected soil samples showed significant and Positive correlation with available N (r=0.48**), available P (r=0.473**), available K (r=0.643**) and available S (r=0.265**). Soil organic carbon showed significant and positive correlation with available N (r=0.326**) and available P (r=0.236**) whereas non-significant and positive correlation with available K and S. Significant and negative correlation was found between electrical conductivity and available N (r= -0.211**). Sand content showed negative correlation with all the macronutrients. Significant and positive correlation showed silt content with available P (r= 0.45**) and available K (r=0.468**). Clay content showed positive and significant correlation with available K (r=0.678**) while non-significant correlation with available sulphur.